Mechanical Ventilation in Patient with Respiratory Failure - Pupella, Rosalia Ameliana (Springer Singapore, 2018)
This handbook covers the principles of mechanical ventilation, making them easy to understand and apply in clinical settings. Presented in an accessible style and supplemented by a wealth of illustrations and graphs, it includes chapters on the basic mathematics and physics of ventilation, respiratory anatomy, basic and advanced ventilation modes, and the fundamentals of acid-base balance. A closing chapter on troubleshooting for mechanical ventilation provides valuable tips on how to deal with various situations encountered in intensive care units. The book is primarily intended for respiratory therapy practitioners, clinicians in pulmonary units, and pulmonologists, as well as graduate students in respiratory medicine and students pursuing undergraduate courses in respiratory therapy - all of whose work involves mechanical ventilators.